2020
DOI: 10.2337/db19-1218
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity and Western-Style Diet Impair Fetal and Juvenile Offspring Skeletal Muscle Insulin-Stimulated Glucose Transport in Nonhuman Primates

Abstract: Infants born to mothers with obesity have a greater risk for childhood obesity and metabolic diseases; however, the underlying biological mechanisms remain poorly understood. We used a Japanese macaque model to investigate whether maternal obesity combined with a Western-style diet (WSD) impairs offspring muscle insulin action. Adult females were fed a control or WSD prior to and during pregnancy through lactation, and offspring subsequently weaned to a control or WSD. Muscle glucose uptake and signaling were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…The adverse nutritional environment in early life might be one of the important factors in deciphering the rapid development of obesity and metabolic disorders. During the last decade, growing numbers of animal experimental models have demonstrated that maternal obesity or HFD resulted in increased offspring susceptibility to metabolic disorders (Campodonico-Burnett et al, 2020;Costa et al, 2020). Concordantly, our study also demonstrated that maternal HFD not only led to glucose and lipid metabolic disturbances in dams but also programmed glucose intolerance and disorders of serum lipid profiles in male offspring from young into adulthood.…”
Section: Discussionsupporting
confidence: 82%
“…The adverse nutritional environment in early life might be one of the important factors in deciphering the rapid development of obesity and metabolic disorders. During the last decade, growing numbers of animal experimental models have demonstrated that maternal obesity or HFD resulted in increased offspring susceptibility to metabolic disorders (Campodonico-Burnett et al, 2020;Costa et al, 2020). Concordantly, our study also demonstrated that maternal HFD not only led to glucose and lipid metabolic disturbances in dams but also programmed glucose intolerance and disorders of serum lipid profiles in male offspring from young into adulthood.…”
Section: Discussionsupporting
confidence: 82%
“…In animal studies, the effects of a control or low-fat post-weaning diet have been investigated. For example, in rats, consumption of a control diet postweaning did not reverse the metabolic phenotype caused by exposure to an obesogenic diet in utero (12), nor did a control postweaning diet restore cardiovascular function in males (70). This suggests that any adverse outcomes of the in utero environment cannot be negated by the postweaning diet.…”
Section: Potential Interventions and Therapeuticsmentioning
confidence: 99%
“…Indeed, a rapidly growing and convergent body of epidemiological, clinical, and experimental evidence in humans and animals suggests that the origins of obesity can be traced, in part, back to developmental processes occurring during the intrauterine period of life, at which time the developing embryo/fetus responds to “suboptimal” conditions by producing structural and functional changes in cells, tissues, and organ systems that persist across the life span and modulate susceptibility for many complex common disorders (i.e., the concept of fetal, or developmental, programming of health and disease risk). To date, research on fetal programming of obesity has focused largely on processes and mechanisms within peripheral cells, tissues, and organ systems, such as adipocyte, 17 pancreas, 18 liver, 19–21 and muscle 22,23 biology. Although this focus is entirely justified, we suggest there is yet another system of critical importance that also warrants attention in the context of fetal programming: the brain circuitry that underlies energy balance homeostasis.…”
Section: Introduction and Overviewmentioning
confidence: 99%